Assessing the role of submarine groundwater discharge as a source of Sr to the Mediterranean Sea. (1st March 2017) - Trezzi, Giada; Garcia-Orellana, Jordi; Rodellas, Valentí; Masqué, Pere; Garcia-Solsona, Ester; Andersson, Per S.
Abstract: Submarine groundwater discharge (SGD) has been identified as an important source of Sr to the ocean and the SGD-driven Sr flux to the global ocean has been recently re-evaluated (Beck et al., 2013). However, the uncertainty of this value is still high because of the uncertainties related to the determination of SGD flow rates and the paucity of 87 Sr/ 86 Sr data in SGD end-members. As carbonates have high Sr concentrations and are subjected to intense heightened weathering, they might significantly influence the SGD input of Sr to the ocean. Here we present data on Sr concentrations and 87 Sr/ 86 Sr ratios in three carbonate dominated sites of the western area of the Mediterranean Sea, a semi-enclosed basin characterized by abundant coastal carbonates. The 87 Sr/ 86 Sr ratios in groundwater were lower compared to modern seawater (∼0.70916), as expected for areas dominated by carbonate lithologies. Concentrations of Sr and 87 Sr/ 86 Sr ratios in groundwater showed conservative mixing in the studied subterranean estuaries. By using SGD flow rates reported in the literature for the study areas, a flow-weighted fresh SGD end-member characterized by a Sr concentration of 27–30 μM and a 87 Sr/ 86 Sr ratio of 0.707834–0.708020 was calculated for the eastern coast of the Iberian Peninsula. Integrating these Sr data with literature data (i.e. values of Sr concentration and 87 Sr/ 86 Sr ratio from other lithologies as well as SGD flow rates), we also calculated the fresh SGD-driven Sr flux to the entire Mediterranean Sea, obtaining a value of (0.34–0.83)·10 9 mol y −1, with a 87 Sr/ 86 Sr of 0.7081–0.7086. Thus, for the entire Mediterranean basin, SGD is globally a source of Sr less radiogenic compared to seawater. The SGD Sr flux to the Mediterranean Sea represents 5–6% of the SGD Sr flux to the global ocean and the Mediterranean SGD end-member has higher Sr concentration (5–12 μM) than the global SGD end-member (2.9 μM). This confirms the significant role of carbonate lithologies on SGD-driven Sr fluxes to seawater. The fresh SGD-driven Sr flux to the Mediterranean Sea is about 20–50% of the riverine Sr input and significantly higher than the input through atmospheric dust deposition. Therefore SGD should be considered as an important continental source of Sr to the basin.